Perspectives of International Apprentice Students in Teaching English as an International Language at Thammislam School, Thailand - Putra Kaste; Rita Harisma (Indonesian Journal of Education and Mathematical Science, 2023)
The international internship program is an excellent platform to open the eyes of prospective educators to see how far English is actively used in each country. The approach used in this study is a qualitative approach presented in a descriptive form. The data collection technique used in this research is document study. Primary data was obtained from the research results on 7 English language education students carrying out a student exchange program at Thammislam Foundation School. With a total of 6 questions from the questionnaire answered by international internship students as their perceptions, the samples were taken using the Google Room media. In this study, it was found that participants from Thai and Indonesian schools had almost the same level of mastery of English morphology.